Broadband plasmon photocurrent generation from Au nanoparticles/ mesoporous TiO2 nanotube electrodes - Wu,X; Zhang,X; Price,D; Ryan,M; Riley,J; Alford,N; Centeno,A; Xie,F (Solar Energy Materials and Solar Cells, 2015)
There has been an increasing interest in plasmon-induced enhancement of solar cells and more recently in the direct generation of photocurrent using noble metal nanoparticles with their Localised Surface Plasmon Resonance (LSPR) in the visual part of the spectrum. In this paper we report broadband plasmon photocurrent generation using novel Au nanoparticle incorporated mesoporous TiO2 nanotube electrodes. Plasmonic induced photocurrent due to hot electrons is observed over a broad wavelength range (~500 to 1000 nm). Incident photon-to-electron conversion efficiency (IPCE) measurements undertaken showed a maximum photocurrent enhancement of 200 fold around 700–730 nm wavelength.